Descriptive epidemiology of COVID-19 in Palembang, Indonesia - Najmah; Setiawan, Yudhi; Yeni; Nurhaliza, Marisa; Azzahra, Hafiza; Yunara, Yulia; Rosyada, Amrina; Fauzia; Fenty Aprina; Misnaniarti (Public Health and Preventive Medicine Archive, 2022)
Background and purpose: Indonesia ranks the first highest mortality rate of COVID-19 in Southeast Asia with an average case fatality rate (CFR) of 2.7%. South Sumatra is ranked 14th out of 34 provinces in Indonesia, with a CFR value related to COVID-19 reaching 5.1%, per June 21, 2021. This study aims to determine the descriptive epidemiology of COVID-19 in Palembang City. Methods: This research used a descriptive epidemiology approach and spatial analysis with the geographic information system. Then the secondary data were collected from the Palembang City Surveillance Report from March 2020 to February 2021 with a total of 7,423 cases, as well as geographic data on the coordinates of health services for all hospitals and public health centers (PHCs) in Palembang City. Results: The data shows that the age group of 25 to 39 years old dominated the COVID-19 cases. The morbidity and mortality rates in men was higher than women, and much higher at the age of above 60 years old. The most dominant symptom in the deceased COVID-19 patients was shortness of breath and the comorbid history increased the risk of death for patients with COVID-19. The highest number of confirmed cases of COVID-19 was found in the sub-district with the highest population, including the PHC of Padang Selasa, Ilir Barat I (393 patients), while the lowest number of cases was reported in Karyajaya PHC, Kertapati (7 patients). Conclusion:This study highlights the need in preventing mature deaths of COVID-19 patients by prioritizing elderlies who suffered from comorbidities at the family level and health services to support the government programs.